The Implementation of the Two Stay Two Stray (Tsts) Learning Model and Co-Op Co-Op for the Improvement of Students’ Learning Outcome in the Crafts and Entrepreneurship Subject - Wardana, L W; Setyani, R; Harwida, G (KnE Social Sciences, 2018)
An effective learning process is created in order to make students able to reach achievement and learning outcome optimally. Based on observations and interviews with teacher of the Crafts and Entrepreneurship Subject, students are less interested or motivated when they did a group task as there were only a few active students in the learning process, while most of the students were late in submitting the tasks given to them and their learning outcome is still under the minimum passing grade. In order to solve the aforementioned problem, the teacher may use an interesting learning model strategy such as Two Stay Two Stray (TSTS) and Co-op Co-op learning model. The goal of this research was to describe the implementation of TSTS dan Co-op Co-op learning model, the students’ learning outcome seen from the cognitive domain after the implementation of TSTS dan Co-op Co-op learning model of Crafts and Entrepreneurship subject. The implementation was conducted in 2 cycles in which each cycle consists of 2 meetings. Also, it was conducted by using 4 steps: planning, implementation, observation, and reflection. The data collection techniques used are observation, test, field note, and documentation. The data analysis techniques in this research used 3 steps: data reduction, data display, and conclusion drawing. The research results showed that the success percentage of teacher activity to the TSTS and Co-op Co-op learning model implementation in cycle I was 86,7% which improved by 7,73% to be 94,43% in the cycle II. The students’ learning outcome towards cognitive domain improved seen from the average score of the cycle I for 69,92 that improved to be 72,85 in the cycle II. The percentage of learning completeness was 60,76% in the cycle I and improved to be 72,44% in the cycle II and had fulfilled the minimum passing grade. One of the constraints occurred in the implementation of TSTS dan Co-op Co-op learning model is that students are not accustomed to giving questions, and arguments when discussing in front of the classroom and preferably the teacher needs to verify the chances of each group in preparing questions for the group in front of the class. Keywords: Two Stay Two Stray (TSTS) Learning Model, Co-op Co-op Learning Model, Learning Outcome, Crafts, and Entrepreneurship Subject